Significant associations between 5-hydroxytryptaminetransporter-linked promoter region polymorphisms of the serotonin transporter (solute carrier family 6 member 4) gene and Thai patients with autism spectrum disorder - Wikrom Wongpaiboonwattana; Oradawan Plong-On; Areerat Hnoonual; Pornprot Limprasert (My University, 2020)
Abstract Autism spectrum disorder (ASD) is a form of pervasive developmental disorder manifested by impairment in social interactions and repetitive behaviors. Although genetic contribution is strongly suspected in autism, the specific genetic factors remain unidentified. Hyperserotoninemia has been reported in some autistic patients, and several studies have demonstrated an association between 5-hydroxytryptamine-transporter-linked promoter region (5-HTTLPR) polymorphisms and rs25531 single nucleotide polymorphism in the serotonin transporter gene (solute carrier family 6 member 4; SLC6A4 ) and ASD, indicating a possible involvement of the serotonin system in the etiology of ASD. To explore this situation further, a case-control association study of 5-HTTLPR and rs25531 polymorphisms on Thai ASD patients was conducted. A total of 188 ASD cases fulfilling the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV) criteria (156 males and 32 females) and a total of 250 normal controls were recruited from the same ethnic backgrounds. 5-HTTLPR polymorphisms (Long, L; Short, S) and rs25531 (A/G) single nucleotide polymorphism were genotyped and compared between the patients and normal controls using chi-square statistics. The L/L genotype was more common in patients than in the controls (13.8% vs 5.2%, P = .006), and the LA haplotype was found in patients more than the controls (16.9% vs 12.2%, P = .048). When male patients were analyzed alone (156 individuals), the associations were also statistically significant with P = .017 for L/L genotype, and P = .019 for LA haplotype distribution. Our findings support previous reports suggesting an association between the 5-HTTLPR and rs25531 polymorphisms of SLC6A4 and patients with ASD.
Keywords: 5-HTTLPR; Autism Spectrum Disorder Research